Harmony: One True Heart - Book 9 - Thomas, Jodi (Thorndike, Maine : Center Point Large Print, 2015)
"As their paths cross in new, captivating directions, the townspeople of Harmony need to learn to love and let go in order to live together in their little slice of heaven"--
Keywords: Large type books